Clinical image of infiltrating lobular breast carcinoma - Skotnicki, Piotr; Ryś, Janusz; Mituś, Jerzy; Jakubowicz, Jerzy; Blecharz, Paweł (Contemporary Oncology/Współczesna Onkologia, 2008)
In our work we present typical features of the clinical image of infiltrating lobular breast carcinoma. We place emphasis on the differences between clinical features and selected microscopic attributes of infiltrating lobular breast carcinoma (ILC) and infiltrating ductal carcinoma of the breast (IDC). In accordance with the literature we found that patients with ILC were older and the tumour medium size was larger than in patients with IDC at the moment of breast cancer detection. Risk of lesion multiplicity and appearance of breast cancer in the other breast is higher in patients with ILC than in patients with IDC. Infiltrating lobular breast carcinoma more often than IDC metastasizes to the peritoneum, periaortic space, gastrointestinal tract, meninges, and gynaecological organs, but rarely to the lungs, pleura or brain. Among patients with ILC the percentage of cancer with high and medium differentiation in the pathological stage is higher than in IDC patients. Despite larger tumour size, metastases to axillary nodes are rare in comparison to patients with IDC. In case of breast conserving therapy in patients with ILC it is more difficult to obtain a surgical margin free from cancer than in patients with IDC.